Remaining Innovative: The Role of Past Performance, Absorptive Capacity, and Internationalization - Ivan Lapuente Garrido; Ronaldo Couto Parente; Cláudio Reis Gonçalo; Sílvio Luís de Vasconcellos (BBR: Brazilian Business Review, 2017)
Emerging markets firms are tardy regarding innovativeness and international orientation. Despite that, some of these firms are becoming increasingly competitive regarding innovation and internationalization. It is still unclear how these firms acquire and maintain an innovative capacity. To address this gap we propose and test a framework that integrates the role of past performance as a proxy to investment capacity, realized and potential absorptive capacity and internationalization and their influences on innovativeness, through a survey of 202 Brazilians firms from the Information Technology industry. The results showed the potential and realized absorptive capacity partially mediates the relationship between past performance and innovativeness, and internationalization moderates the relationship between potential absorptive capacity and innovativeness.